CLASSICAL THEISM new essays on the metaphysics of god. - Fuqua, Jonathan; Koons, Robert C. ([S.l.] : ROUTLEDGE, 2023)
This volume provides a contemporary account of classical theism. It features 17 original essays from leading scholars that advance the discussion of classical theism in new and interesting directions. It's safe to say that classical theism--the view that God is simple, omniscient, and the greatest possible being--is no longer the assumed view in analytic philosophy of religion. It is often dismissed as being rooted in outdated metaphysical systems of the sort advanced by ancient and medieval philosophers. The main purpose of this volume is twofold: to provide a contemporary account of what classical theism is and to advance the scholarly discussion about classical theism. In Section I, the contributors offer a clear and cutting-edge account of the nature and existence of the God and the historical and theological foundations of classical theism. Section II contains chapters on a variety of topics, such as whether classical theism's doctrine of simplicity needs revision, whether simplicity is compatible with the Christian doctrine of the Incarnation, and whether the hypothesis of a multiplicity of divine ideas is consistent with divine simplicity, among others. Classical Theism will appeal to scholars and advanced students in the philosophy of religion who are interested in the nature of God.
Keywords: Metaphysics; God; PHILOSOPHY / Religious; RELIGION / Theism